Characterization of phase change material (paraffin wax) for thermal energy storage - Low, Jin Quan (2019)
For a long time, researchers have been trying to reduce the use of non-renewable energy sources. One of the methods, which has been of growing popularity, is to make use of waste heat energy from human activities and the use of Phase Change Materials (PCMs) to store such energy. Hence, this experiment aims to characterize the melting of PCM in heat sinks with different pin fin structures. It is hoped that the results obtained from this investigation will be useful for design of thermal energy storage devices. This was done by exploring the performance of pin fin-based heat sinks with different configurations and determine the effects they had on melting characteristics of the PCM. PCM based heat sinks of similar base areas but with differing pin fin configurations were used in this study. All the pin fins also have a constant height of 20 mm but varied in diameter, fin number, longitudinal pitch and lateral pitch. The fins were kept at a constant volume ratio to enclosed area ratio. An empty heat sink without fins was also used and it serves as comparison against the pin fin heat sinks. The heat sinks were subjected to a constant wall temperature and the same initial conditions. The data collected from the experiments were compared to an empty heat sink. The results showed that the addition of pin fin structures significantly reduces the time required to initiate phase change and the melting time. The results also showed that the pin fin diameter (ϕ) of 3 mm was able to charge the PCM to its steady-state temperature faster and that the effects of natural convection would be negated with smaller fin pitch as it impedes the formation of convection current. The comparison between pin fins of ϕ = 3 mm and ϕ = 4 mm revealed that better performance of PCM heating under steady state conditions and this was mainly attributed to the enhancement of total effective surface area for heat transfer. The study concludes by stating the reasons for the respective heat transfer phenomena and recommends the addition of chiller systems for future studies to characterize the discharging process of PCM.